Search for supersymmetry in pp collisions at [Formula: see text] TeV in events with a single lepton, jets, and missing transverse momentum - CMS Collaboration; Chatrchyan, S; Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; et al. (The European physical journal. C, Particles and fields, 2013)
UNLABELLED: Results are reported from a search for new physics processes in events containing a single isolated high-transverse-momentum lepton (electron or muon), energetic jets, and large missing transverse momentum. The analysis is based on a 4.98 fb-1 sample of proton-proton collisions at a center-of-mass energy of 7 TeV, obtained with the CMS detector at the LHC. Three separate background estimation methods, each relying primarily on control samples in the data, are applied to a range of signal regions, providing complementary approaches for estimating the background yields. The observed yields are consistent with the predicted standard model backgrounds. The results are interpreted in terms of limits on the parameter space for the constrained minimal supersymmetric extension of the standard model, as well as on cross sections for simplified models, which provide a generic description of the production and decay of new particles in specific, topology based final states. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1140/epjc/s10052-013-2404-z) contains supplementary material, which is available to authorized users.